TINJAUAN YURIDIS TERHADAP PENGGUNAAN KARTU TANDA PENGENAL ADVOKAT TIDAK VALID SEBAGAI PELANGGARAN KODE ETIK - Aulia Hermastuti Turastananing Sari; Arsyad Aldyan (Sebelas Maret University, 2025)
This article examines the use of an invalid Advocate Identification Card (KTPA) as a violation of the code of ethics, and explores its long-term effects on the credibility of the legal profession. The use of invalid KTPA in the judicial process can harm justice and threaten the integrity of the legal system. This practice not only reflects weaknesses in the lawyer's identity verification process, but also has the potential to result in unfair court decisions due to the presence of unauthorized parties. The purpose of this article is to find out the legal sanctions that can be given to advocates who have violated the code of ethics due to the use of an invalid KTPA. This article was researched using empirical legal research methods. The research results prove that the use of an invalid KTPA in the judicial process is considered a violation of the code of ethics. Therefore, it is important for the legal system to enforce sanctions for violations of this kind in order to maintain the integrity and credibility of the advocacy profession and the justice system as a whole. The sanctions that will befall the advocate range from ordinary warnings, strong warnings, temporary dismissal, to expulsion from membership in professional organizations.